Energy Harvesting Combat Boot for Satellite Positioning - Haluk Akay; Ruize Xu; Dexter Chew Xuan Han; T. Hui Teo; Sang-Gook Kim (Micromachines, 2018)
Most portable electronic devices are power-limited by battery capacity, and recharging these batteries often interrupts the user’s experience with the device. The product presented in this paper provides an alternative to powering portables by converting regular human walking motion to electricity. The device harvests electric power using air bulbs, distributed in the sole of a shoe to drive a series of micro-turbines connected to small DC motors. The number and position of air bulbs is optimized to harvest the maximum airflow from each foot-strike. The system is designed to continuously drive the micro-turbines by utilizing both outflow and inflow from the air bulbs. A prototype combat boot was fitted on the right foot of a 75 kg test subject, and produced an average continuous power on the order of 10 s of mW over a 22 Ω load during walking at 3.0 mph. This combat boot provides enough electric power to a passive GPS tracker that periodically relays geographical coordinates to a smartphone via satellite without battery replacement.